Microbial Pigment Production for Sustainable Production: a review - aisyah, nur; binti Abdullah, Shakila (Vietnam Journal of Science and Technology, 2025)
Microbial pigments have great potential and strength to produce natural color on an industrial scale at an affordable cost. However, their development faces challenges due to the presence of inexpensive synthetic pigments dominating the market. These synthetic pigments often contain azo dyes, which are harmful to human health and the environment. Hence, there is an urgent need for regulations, prevention measures, and research to shift from synthetic to natural pigments. Despite this, microbial pigments are gaining attention as alternatives in various industries. Challenges in producing them on an industrial scale include pigment stability, product shelf life, and expensive raw materials. This review aims to provide a systematic and precise description of how microbial pigments are developed from raw materials, outlining specific phases for their production. Additionally, it will highlight technological challenges and limitations faced in their utilization.